Concept Analysis of Presenteeism Among Nurses During the COVID-19 Pandemic - Jiyeon Jung; Jihyun Moon (SAGE Open Nursing)
Introduction Presenteeism is a significant issue among nurses, especially during the COVID-19 pandemic, contributing to high healthcare costs, impaired patient safety, and negative well-being. Given the global nursing shortage and the critical role nurses play in healthcare, addressing presenteeism is essential to maintaining quality care and organizational efficiency. Objectives This study aimed to clarify the concept of presenteeism among nurses, the largest proportion of healthcare professionals, during the COVID-19 pandemic. Method Walker and Avant's concept analysis procedure was adapted to clarify the conceptualization and operationalization of the concept. The Cumulative Index of Nursing and Allied Health, PUBMED, EMBASE, and Research Information Sharing Service were systematically searched for the analysis. Results Presenteeism among nurses during the pandemic was conceptualized as work impairment with a detachment of mind and body and disengagement among nurses when present at the workplace. The antecedents of presenteeism in nursing were health problems, worsened work conditions, risk of infection, and the uniqueness of the nursing culture. The consequences included work productivity loss and deterioration in quality of care and patient safety. Conclusions Presenteeism among nurses is a complex phenomenon that may influence their job satisfaction and patient health outcomes. Nurses being the most affected frontline workers by the pandemic, nursing managers need to be aware of this phenomenon and try to prevent nurses with health problems to work by adopting organizational policies that allow them to treat their conditions effectively. In addition, nurses should be properly informed and treated for presenteeism and its effects.